Comparison of Thermodynamic, Kinetic Forces for Three NADH Analogues to Release Hydride Ion or Hydrogen Atom in Acetonitrile. Issue 31 (17th August 2021) - Fu, Yan‐Hua; Shen, Guang‐Bin; Wang, Kai; Zhu, Xiao‐Qing
Abstract: In this work, the thermodynamic and kinetic forces of three NADH analogues as BNAH, HEH2, and AcrH2, to release hydride ion or hydrogen atom in acetonitrile in chemical reactions were discussed and researched, which was important for chemists to understand the real capacity of hydride‐donating, hydrogen‐atom‐donating of these three compounds. By comparing the bond dissociation free energy [Δ G o (XL)], self‐exchange reaction activation energy [Δ G ≠ XL/X ], and thermo‐kinetic parameter [Δ G ≠ °(XL)] of these three compounds to release hydride ion or hydrogen atom, it's easy to find that reactions that thermodynamically favorable were not necessarily kinetically favorable. Therefore, it's unreasonable to judge the hydride‐donating ability or hydrogen‐atom‐donating ability of a compound only by its thermodynamic parameter or kinetic parameter. In addition, with these thermodynamic and kinetic parameters, we are better able to select suitable compound as model of NADH which based on different requirement in reactions. Abstract : The thermodynamic, kinetic forces for three NADH analogues BNAH, HEH2, AcrH2 to release hydride ion and hydrogen atom in acetonitrile are compared. The paper suggests to use the thermo‐kinetic parameters to evaluate the reactivity's of the dihydropyridines.